2020
DOI: 10.1007/s00261-020-02449-y
|View full text |Cite
|
Sign up to set email alerts
|

Management algorithm of acute cholecystitis after percutaneous cholecystostomy catheter placement based on outcomes from 377 patients

Abstract: Background. Acute cholecystitis in severely cardiopathic patient after major cardiac surgery represent a challenge for surgeons. Treatment with cholecystostomy could represent a chance for patients even if there are many topics of greatest debate about it: the technique of performing it (if transhepatic or transpapillary), the timing of optimal duration, the timing of drain removal, the need of further examinations before the removal as well as the timing for de nitive surgery. We therefore deemed important to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Tube removal is suggested 3-6 weeks after placement because of tract maturation. However, the mean tube removal time was reported as 89 days in the literature [8]. Major or minor complication rate varies from 2.4 to 16%, and mortality rate ranges between 0-1.4% [9].…”
Section: Introductionmentioning
confidence: 99%
“…Tube removal is suggested 3-6 weeks after placement because of tract maturation. However, the mean tube removal time was reported as 89 days in the literature [8]. Major or minor complication rate varies from 2.4 to 16%, and mortality rate ranges between 0-1.4% [9].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al[ 4 ] showed that an elective delayed LC after PC decreases conversion and complication rates in AC, although it increases hospital stay and patients have the inconvenience of a cholecystostomy tube. PC remains a viable option for the treatment of AC with a low complication rate and can be used as a bridge to definitive therapy[ 5 ]. Meanwhile, one study found that cholecystostomy may cause fibrosis during the healing process, eventually complicating LC[ 6 ].…”
Section: Introductionmentioning
confidence: 99%